Qi-Dong-Huo-Xue-Yin balances the immune microenvironment to protect against LPS induced acute lung injury - zhao, Tian; Wang, Le; Zhang, Yongjun; Ye, Wu; Liu, Juan; Wu, Haiyan; Wang, Fei; Tang, Tingyu; Li, Zhijun (Frontiers in Pharmacology, 2023)
COVID-19 induces acute lung injury (ALI)/acute respiratory distress syndrome (ARDS) and leads to severe immunological changes that threatens the lives of COVID-19 victims. Studies have shown that both the regulatory T cells and macrophages were deranged in COVID-19-induced ALI. Herbal drugs have long been utilized to adjust the immune microenvironment in ALI. However, the underlying mechanisms of herbal drug mediated ALI protection are largely unknown. This study aims to understand the cellular mechanism of a traditional Chinese medicine, Qi-Dong-Huo-Xue-Yin (QD), in protecting against LPS induced acute lung injury in mouse models. Our data showed that QD intrinsically promotes Foxp3 transcription via promoting acetylation of the Foxp3 promoter in CD4+ T cells and consequently facilitates CD4+CD25+Foxp3+ Tregs development. Extrinsically, QD stabilized β-catenin in macrophages to expedite CD4+CD25+Foxp3+ Tregs development and modulated peripheral blood cytokines. Taken together, our results illustrate that QD promotes CD4+CD25+Foxp3+ Tregs development via intrinsic and extrinsic pathways and balanced cytokines within the lungs to protect against LPS induced ALI. This study suggests a potential application of QD in ALI related diseases.